Toward a framework of financial wellness determinants: investigating the moderating effect of religion - Sabri, Mohamad Fazli; Falahati, Leila (American-Eurasian Network for Scientific Information, 2014)
Financial wellness and its impact on personal and family life satisfaction have received considerable attention from research scholars, financial counselors and even family economics in recent decades. A large number of studies have attempted to identify the factors that significantly predict financial wellness among various groups in relation to the development of personal financial wellness. In order to determine the main determinant of financial wellness, several factors were considered including money attitude, financial socialization, secondary socialization agent influence, primary socialization agent influence, financial knowledge, financial management and financial problem. The purpose of this paper is to investigate the moderating effect of religion in predicting financial wellness. For this purpose, data was gathered from public and private university students throughout Malaysia. The findings of this study verify that religion has a moderating effect on financial wellness. The results further reveal that there are differences between Muslim and Non-Muslim students with regard to financial matters and practices, which in sum results reveal the greater effect of secondary socialization agents on Non-Muslim students, while for Muslim students, the effect of their financial knowledge and primary socialization agents, including parents and religion is greater. Considering the crucial role of parents in the socialization of their children in financial matters, the implication of this finding becomes even more obvious for family economics and financial educators.